Processor description languages : - Mishra, Prabhat (Morgan Kaufmann Publishers/Elsevier, 2008)
This book is the first, comprehensive survey of modern architecture description languages and will be an invaluable reference for embedded system architects, designers, developers, and validation engineers. Readers will see that the use of particular architecture description languages will lead to productivity gains in designing particular (application-specific) types of embedded processors.